Summary Guidance Note — Climate resilience in displacement: Examining UNHCR’s SuLMER intervention in Cox’s Bazar, Bangladesh - Vaselli, Alessandra; Khalid, Shahab; Savelli, Adam; Craparo, Alessandro; Basel, Ashleigh; Minoarivelo, Henintsoa Onivola; Tsoka, Jonathan; Dao, Hoa; Suza, Ma; Barua, Nipul; Hoque, Md. Ehsanul; Sarma, Santanu; et al. (2025)
This Summary Guidance Note outlines key results and recommendations from the Full Report. The CGIAR Science Program on Food Frontiers and Security’s partnership with the United Nations High Commissioner for Refugees (UNHCR) aims to advance climate action and strengthen protection, climate resilience, and peace for forcibly displaced and stateless people. In response to recurring floods and general environmental degradation, in 2019 UNHCR began developing the Sustainable Land Management and Environmental Rehabilitation (SuLMER) intervention that is currently being implemented in Camps 1W and 2W. SuLMER aims to mitigate environmental hazards and reduce pollution by increasing water flow, reducing solid waste, stabilising unsteady hillside slopes, decommissioning WASH facilities that were non-functional or susceptible to contamination, and introducing nature-based solutions for environmental challenges. This research aimed to explore how the SulMER intervention contributed to the subjective resilience of target households, and how resilience gains affect humanitarian, development, and peacebuilding outcomes. Methods consist of a quantitative mapping of baseline (current) and projected climate hazards (by 2040), an n=539 survey of intervention participants, several weeks of field observation, and key informant interviews with intervention participants, community leaders, UNHCR staff, and UNHCR’s implementing partners. Results show that climate hazards will worsen in Cox’s Bazar by 2040 and that, by improving households’ self-reported environmental security, SuLMER enhanced households' subjective resilience to anticipate, withstand, recover from, and transformatively adapt to future hazards. However, structural barriers to transformative adaptation, sustainable development, and social cohesion remain for Rohingya refugees in the camps.